Contraceptive Pharmacology and Risk Communication: A Case-Based Flipped Classroom Exercise - Joseph Ottolenghi; Gagani Athauda; Sarah E. Stumbar; Sanaz B. Kashan; Carla Lupi (Association of American Medical Colleges, 2019)
Introduction Oral contraceptives are widely used for both contraceptive and noncontraceptive purposes. Of women ages 15-44 who have ever had sexual intercourse, 88% have used at least one hormonal contraceptive method. Health care providers caring for reproductive-age women need a strong base of knowledge in hormonal contraception. Those who provide contraceptive counseling must apply this knowledge to shared decision making, including effective quantitative communication. Methods Students and faculty at Florida International University Herbert Wertheim College of Medicine created a prerecorded lecture and in-class interactive case on contraceptive pharmacology and risk communication. The 20-minute lecture focused on mechanisms of action, bioavailability, drug-drug interaction, effectiveness, and major vascular risks of combined hormonal and progestin-only contraceptives. The 55-minute in-class session integrated knowledge of risks and effectiveness of contraception with risk communication surrounding contraceptive decision making and counseling. For the 2018 academic year, 122 first-year medical students participated in the session. Students anonymously answered three questions related to the session on their end-of-course evaluation. Student learning was assessed with five multiple-choice questions on the pharmacology final exam. Results Students rated the session very positively. They highly rated the lecture's utility and the sesssion's contribution to solidifying their basic science knowledge and understanding of its clinical applications. Class average performance on the relevant final exam questions was 88.4%. Discussion The lecture and case discussion successfully addressed gaps in the curriculum and provided students the opportunity to integrate multiple domains of learning. Students' perception of the materials was positive, and they demonstrated adequate learning.